2017
DOI: 10.1177/1469066717722256
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric characterization of protein structures and protein complexes in condensed and gas phase

Abstract: Proteins are essential for almost all physiological processes of life. They serve a myriad of functions which are as varied as their unique amino acid sequences and their corresponding three-dimensional structures. To fulfill their tasks, most proteins depend on stable physical associations, in the form of protein complexes that evolved between themselves and other proteins. In solution (condensed phase), proteins and/or protein complexes are in constant energy exchange with the surrounding solvent. Albeit met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 162 publications
(165 reference statements)
1
13
0
Order By: Relevance
“…Matching with this experimental observation, our in-silico simulations indicated that remaining forces that held the S-peptide complexed to the S-protein in the gas phase, i.e., after evaporation of solvent were consistent with previous estimations where subtle structural changes of protein surface amino acid residues (of protein complexes) in the gas phase were described to take place while simultaneously the protein ions maintained their over-all solution-like structures [24,32,33]. One limitation when choosing the force field for gas-phase simulations of protein structures is parametrization, as published parameter sets are available only for the neutral forms of amino acids.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Matching with this experimental observation, our in-silico simulations indicated that remaining forces that held the S-peptide complexed to the S-protein in the gas phase, i.e., after evaporation of solvent were consistent with previous estimations where subtle structural changes of protein surface amino acid residues (of protein complexes) in the gas phase were described to take place while simultaneously the protein ions maintained their over-all solution-like structures [24,32,33]. One limitation when choosing the force field for gas-phase simulations of protein structures is parametrization, as published parameter sets are available only for the neutral forms of amino acids.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the rich data background on RNAse S, this commercially available non-covalent protein–peptide complex with clearly defined molecular composition is an ideal substance for developing methods by which supramolecular properties as well as influences of the solution environment can be elucidated in both the condensed and the gas phase. The desire to apply mass spectrometry for determining binding strengths of non-covalent forces, i.e., affinities between biomolecules was expressed already from early on [ 6 ] taking solution chemistry and biophysical concepts as models [ 24 ]. Our quantitative data on RNAse S dissociation in the gas phase substantiate the interpretation that interfering with polar interactions between S-peptide and S-protein by in-solution pH changes is resembled by a shift in mean charge states of the protein complex in the gas phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the relatively low amounts of samples required (19) and the rapidity (6) by which mass spectrometric epitope mapping is executed is of great advantage in this respect (20). Chemical cross-linking mass spectrometry (21,22), hydrogen/deuterium exchange (HDX) 1 mass spectrometry (23) and mass spectrometric methods that employ chemical modification on proteins, such as Fast Photochemical Oxidation of Proteins (FPOP) (24,25) or chemical modification of surface exposed residues (26,27) have been applied in epitope mapping experiments (28) and in determinations of protein -protein interaction sites in general (29), but their application may be limited when rather demanding chemistries are involved, or when performing such experiments becomes laborious, and/or requires sophisticated laboratory equipment (20,30). Significant advances in epitope mapping protocols/methods have been reached with the two most commonly used mass spectrometric methods: epitope extraction and epitope excision (20,31,32).…”
Section: Intact Transition Epitope Mapping -Targetedmentioning
confidence: 99%
“…Interestingly the trends of the gas phase values pretty much resembled those from the in= As shown here, dissociation energies of protein=protein complexes in the gas phase that have been corrected for "external energy" contributions seem to represent in=solution properties of protein=protein complexes well. As was pointed out in a recent review [30], surface induced dissociation (SID) seems to be an alternative to CID breakage of non= covalent bonds in the gas phase [31,32]. However, in SID experiments charges are distributed proportionally to the masses of dissociated constituents [33].…”
Section: # % #mentioning
confidence: 99%